PERAN â€œFANTASTIC FOURâ€ PADA GAGAL JANTUNG FRAKSI EJEKSI MENURUN - Muhammad Perdana Airlangga; Dwi Wulandari (Universitas Muhammadiyah Surabaya, 2023)
For all patients with heart failure with reduced ejection fraction (HFrEF), a multimodal approach is necessary, with a combination of numerous medications serving as the cornerstone for symptomatic and prognosis improvement. Newer treatment consist of Angiotensin-converting enzyme (ACE) inhibitors, angiotensin receptor/neprilysin inhibitors (ARNI), beta-blockers mineralocorticoid receptor antagonists (MRAs), and sodium-glucose co-transporter 2 (SGLT2) inhibitors demonstrated a highly significant and clinically relevant reduction in mortality and heart failure hospitalizations, as well as an improvement in quality of life.Keywords : heart failure, ejection fraction, ARNI, SGLT-2 inhibitor, ACE inhibitor, beta blocker, MRA